Pendampingan dan aktualisasi kader sebagai edukator pencegahan HIV/AIDS dan seks pranikah di Distrik Sentani, Papua - Utami, Theresia Febriana Christi Tyas; Kismiyati, Kismiyati; Sahiddin, Muhamad; Sunarti, Sunarti (Jurnal PADE: Pengabdian & Edukasi, 2025)
The high prevalence of HIV/AIDS and premarital sexual behavior among adolescents is a significant public health concern in Papua. To address this issue, community service activities were conducted through two main programs: training cadres as health educators for HIV/AIDS prevention and premarital sex and cadre-led activities for adolescent health screening and reproductive health education at YPKP Junior High School in Sentani. The methods used included lectures, discussions, and hands-on practice. The evaluation was carried out using pre-test and post-test assessments to measure changes in the cadres' knowledge, which were analyzed with the Wilcoxon test. The results showed an increase in the average knowledge score of cadres after the training, from 15.6 to 18. The cadres were able to conduct adolescent screenings and provide counseling sessions. This activity effectively enhanced the capacity of adolescent cadres as agents of change and can be sustainably implemented to support HIV/AIDS and premarital sex prevention efforts in other regions.Keywords:  Adolescents, HIV/AIDS, premarital sex, reproductive health, cadre empowerment